The Impact of Positive Discipline on Students’ Well-being and Academic Achievement: A Case of International School in Cairo - Elkadi, Enas; Sharaf, Rasha (European Scientific Journal, ESJ, 2023)
This research is designed to identify the scope of positive discipline implementation as a classroom management approach in Groupe Scholaire Oasis (an international School in Cairo City) by investigating PD’s impact on students’ well-being, and academic achievement. The literature review covered in this research shed light on classroom management, and positive discipline as a classroom management approach and its relation to students’ well-being and academic achievement. To explore how positive discipline as a Classroom Management Approach impacts students’ well-being and academic achievement, researchers used the “Quantitative Method” by applying questionnaires to samples of students from two different age groups: (1) 233 students from grades 3 – 5 (20 % of the whole population), and (2) 367 students from grades 6 – 12 (20 % of the whole population). The Social Sciences Statistical Package SPSS ver.22 was used to perform statistical analyzes. "Mann-Whitney test" for the independent groups was used to examine the equivalence in the Positive Discipline Scale between the group of students, and its significance was verified by the value of (U). In addition, the Pearson correlation coefficient was used to find the correlation between the Positive Discipline variable and the achievement variable for students. Data analysis has indicated that "PD has a positive impact on students from the two different age target groups" with regard to the three variables: PD seven abilities, student: well-being, and approach to learning (ATL) skills. On the other hand, PD’s impact on students’ well-being and academic achievement differs according to age. The results have indicated that the 3 - 5 grades group was superior to the 6 - 12 grades group with regard to: PD Seven Abilities, Student: Well-Being, and Approach to Learning (ATL) Skills. In this context, the researchers recommended raising awareness between administrators, teachers, and parents in coordination with the various administrative authorities to spread the idea and principles of positive discipline, creating a common vision between stakeholders, adopting a strategic governance model that allows continuous monitoring, evaluation, and review of strategies and action plans, creating a positive learning environment, and building the capacity of all the parties involved to enable them from the implementation process.